The Psychiatrist as Novelist in Contemporary Turkish Literature: Pushing the Boundaries of the Real - Alkan, Burcu (Border Crossing, 2018)
In the past decade, several psychiatrist-novelists established a niche for themselves in Turkish literature and their works draw interest from both their particular readership and the broader literary circles. It is not unusual for the members of a medical field that is preoccupied with understanding the psyche through personal narratives to turn toward a realm that have similar motivations. However, the limited number of such writers globally renders this trend in Turkish literature unique. Furthermore, the works of these psychiatrist-novelists stand out with their pushing the boundaries of the real in various ways. Narratives of pathology, science, and fantasy predominate their ouvre. This article argues that the high number of psychiatrist-novelists in contemporary Turkish literature and their preference over narratives that challenge the concept of reality are related to their profession. It discusses how their personal and professional experiences in medicine manifest as a key influence in their creative endeavours.